Pelatihan Penggunaan Aplikasi Canva Sebagai Media Pembelajaran Kreatif Bagi Guru-Guru Di Kecamatan Bulukumpa: Pelatihan Penggunaan Aplikasi Canva Sebagai Media Pembelajaran Kreatif Bagi Guru-Guru Di Kecamatan Bulukumpa - Saiful Saiful; Hamid Ismail; Muh Arief Mukhsin; Rina Asrini Bakri; Andi Mulawakkan Firdaus (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: The purpose of this activity is to provide learning to teachers so that they can carry out an effective and enjoyable learning process to increase student interest in learning. Method: This training is to start with the analysis stage by asking the teachers at SDN 239 Sarajoko problems regarding the online learning process through the zoom application with 13 teachers at SDN 239 Sarajoko and also carried out offline. then design and carry out Canva application training as a learning medium by presenting material after which there is a question and answer session and an evaluation stage of the training results to measure the progress of the results of the training to partners and the final stage of this training is the consultation stage which is carried out so that they continue to carry out communication relationships with partners and service teams. Results: The results of this dedication can be described in several stages, namely the 3 indicators that are the focus of the service team to be implemented in the program are the Canva application in making videos, power points, posters as learning materials. This Canva application training activity really helps teachers to improve their ability to provide modern and effective teaching methods that will make the learning process systematic and comfortable.